The Influence of Mental Workload and Individual Characteristics on Work Stress - Aprilia, Shahnaz; Setyaningsih, Yuliani; Dewi, Endah Kumala (GLOBAL HEALTH SCIENCE GROUP, 2024)
Work stress is a problem that is often faced by employees in various industrial sectors, including in the electricity sector. One of them is the electricity sector at the state-owned company PT X Site Jakarta Raya. Prolonged work stress can have a negative impact on employee performance and well-being. Work stress can cause physiological, psychological and behavioral changes in employees. Data shows that the resignation rate for employees at PT X is quite high. The significant rate of employee resignation in recent years shows that work stress is a problem that needs to be taken seriously. Therefore, this topic needs further research. This research aims to analyze the influence of mental workload and individual characteristics on work stress among employees at the state-owned company PT X Site Jakarta Raya. The method used in this research is quantitative with a purposive sampling technique. In this study there were 125 samples. Data was collected using standard questionnaires from the NIOSH Generic Job Stress Questionnaire (GJSQ) with 41 questions for work stress and NASA-TLX with 15 questions for mental workload. Next, the data was tested using T test analysis. The results of the T test hypothesis analysis show that mental workload (significance = 0.003) and marital status (significance = 0.006) have a significance value of <0.05. Therefore, Ha is accepted and H0 is rejected. Conclusion: Mental workload and marital status have a partially significant influence on the dependent variable of work stress.